KEJAHATAN JABATAN DALAM PERSPEKTIF NEGARA HUKUM PANCASILA - Anjari, Warih (E-Journal Widya Yustisia, 2018)
Official crime is a crime committed by civil servants using the power, facilities and infrastructure of his position. Officials as bearers of the state's mandate, are not allowed to use their positions to commit crimes. The Criminal Code aggravates officials who use their positions to commit crimes under Article 52. The practice of ransom under Article 52 of the Criminal Code is rarely applied to public servants committing crimes. The purpose of writing in this paper is: to describe the setting of crime of office in Indonesian criminal law, and to analyze the application of Article 52 of the Criminal Code against crime of office in the perspective of Pancasila law state. The research method is normative juridical with approach of legislation and case approach. Data used secondary data with qualitative descriptive analysis and systematic interpretation. The conclusion is that the crime of office is regulated in Book II and Book III of the Criminal Code and the penalty for offenses based on Article 52 of the Criminal Code and the objections under Article 52 of the Criminal Code against offenses in line with the implementation of the balance of rights and obligations in the Pancasila state law.